MENYOAL OTENTISITAS HADITS DUA BELAS KHALIFAH - Ahmad Khoirul Fata; Muh. Hukkam Azhadi (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
After the death of Prophet, Muslims are faced with issues that divided and conflicted the ummah up for a long time. To defend its interests, each side try to build their own arguments. One of them is the Shi'a belief in twelve imams. They used the traditions which believed from the Apostle to legitimate their conviction. This study examine the validity of the traditions that are used by Shiites in conceptualize leadership of ummah. The approach used is to test the quality of sanad of the twelve caliphs tradition used among Shiites. keywords: Hadits, Syi'ah, khalifah, sanad, rawi